Grappling with legacies of pain, shame, and blame in independent schools: Reclaiming lament and refocusing praise through Psalm 22 - Spencer, Michael E. (Anglican theological review, 2023)
As many schools grapple with issues of sexual misconduct and legacy abuse, this article revisits the thinking of Walter Brueggeman and Rolf Jacobson and the “costly losses” initiated by a displacement of the psalmic traditions of lament and praise. The article explores the shift from the social gospel to the prosperity gospel. Drawing from the work in theology and trauma studies by Shelly Rambo and Serene Jones, the article considers the power of lament psalms, most specifically Psalm 22, in providing a theological, trauma-informed framework that witnesses to those who have suffered sexual abuse. Moving beyond institutional apology, lament opens the opportunity for grappling with legacies of pain, shame, and blame while confronting the ethos in which lament and praise were lost. Ultimately, reclaiming lament and refocusing praise will require a collaborative commitment by survivors and institutions joining voices to move toward healing, forgiveness, justice, and restoration.